Quality of life in caregivers of patients with multiple myeloma - Pereira, M. Graça (2020)
Objectives: This study aimed to assess the relationship between sociodemographic, clinical, and psychological variables with quality of life (QoL) and the moderating role of caregivers' age and caregiving duration in caregivers of patients with Multiple Myeloma.Method: The sample included 118 caregivers who completed questionnaires that assessed psychological morbidity, satisfaction with social support, coping, burden, unmet needs, and QoL.Results: High psychological morbidity, burden and information, financial and emotional unmet needs were associated with lower QoL, while higher satisfaction with social support and more effective use of coping strategies were associated with better QoL. Women caregivers reported more satisfaction with social support and those who did not choose to care reported greater financial unmet needs and more use of coping strategies. The relationship between caregivers' psychological morbidity/social support and QoL was mediated by emotional needs and double mediated by coping and burden. The caregivers' age moderated the relationship between psychological morbidity/social support and emotional needs.Conclusion: Interventions to support the caregiver's emotional needs to promote their QoL are needed. These should be particularly tailored for older caregivers reporting greater psychological morbidity and younger caregivers less satisfied with their social support, as they have a negative indirect impact on their QoL.